2010
DOI: 10.4103/0970-2113.68306
|View full text |Cite
|
Sign up to set email alerts
|

Utility of fiberoptic bronchoscopy in diagnosis of various lung conditions: Our experience at rural medical college

Abstract: Aim:To evaluate the utility of fiberoptic bronchoscopy in order to find out the etiology in various lung conditions.Materials and Methods:Fiberoptic bronchoscopy was performed in 120 adult patients who had persistent opacities on chest radiography in the form of collapse, consolidation, hilar mass and cavity with proper antibiotic course of 1 to 3 months. Bronchoscopic aspirates, brushing and biopsy (as and when required) were taken. Patient with known lung cancer, sputum positive pulmonary TB, recent myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In another study the diagnostic yield was 75%. 8 Around one-third of the patients in our study had mitotic lesion in bronchoscopy. In another one-third cases, bronchoscopy showed inflammatory lesion and in rest one-third cases the findings were normal.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In another study the diagnostic yield was 75%. 8 Around one-third of the patients in our study had mitotic lesion in bronchoscopy. In another one-third cases, bronchoscopy showed inflammatory lesion and in rest one-third cases the findings were normal.…”
Section: Discussionmentioning
confidence: 69%
“…Badhke et al found pneumonias in 26.6%, malignancy in 23.3%, pulmonary TB in 16.6% cases and in 25% patients no specific diagnosis was made. 8 Among 41 cases of histologically proved bronchial carcinoma, squamous cell type was the predominant type (43.9%), followed by large cell carcinoma (26.8%). This is similar to previous pattern of histological type of bronchial carcinoma, but contrary to the present trend of rising proportion of adenocarcinoma.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…26 BAL, bronchial brushing, bronchial washing and forceps biopsy under direct vision helped in the yield for detection of lung cancer in the present study, the yield was observed in 31 (17.4%) cases out of total bronchoscopy cases (n=178). The yield was 31.11% in one study and upto 11% in another study by Johnson JL et al 27,28…”
Section: Discussionmentioning
confidence: 85%
“…In lung malignancy; FOB helps in early detection of lung cancer by providing an avenue for inspection of peripheral airways including those of the upper lobes. FOB provides histological diagnosis in between 60% to 80% of cases without serious complications (3,4) . FOB is performed for various indications.…”
Section: Introductionmentioning
confidence: 99%